A High‐Throughput Nanofluidic Device for Exosome Nanoporation to Develop Cargo Delivery Vehicles. Issue 35 (21st July 2021) - Hao, Rui; Yu, Zitong; Du, Jing; Hu, Shi; Yuan, Chao; Guo, Hang; Zhang, Yi; Yang, Hui
Abstract: Efficient loading of various exogenous cargos into exosomes while not affecting their integrity and functionalities remains a major challenge. Here, a nanofluidic device named "exosome nanoporator (ENP)" is presented for high‐throughput loading of various cargos into exosomes. By transporting exosomes through nanochannels with height comparable to their dimension, exosome membranes are permeabilized by mechanical compression and fluid shear, allowing the influx of cargo molecules into the exosomes from the surrounding solution while maintaining exosome integrity. The ENP consisting of an array of 30 000 nanochannels demonstrates a high sample throughput, and the working mechanism of the device is elucidated through experimental and numerical study. Further, the exosomes treated by the ENP can deliver their drug cargos to human non‐small cell lung cancer cells and induce cell death, indicating the potential opportunities of the device for developing new exosome‐based delivery vehicles for medical and biological applications. Abstract : A nanofluidic device, named "exosome nanoporator (ENP)", is developed for high‐throughput loading of various cargos into exosomes while not negatively affecting their integrity and functionalities. This technique dynamically exploits the nanofluidic technology on exosome nanoporation, demonstrating the suitability of the ENP as a robust and versatile tool to develop new exosome‐based delivery vehicles for therapeutics and diagnostics.